Isu Gender Dalam Pendidikan Islam: Tantangan Dan Strategi Mewujudkan Keadilan Akses Belajar - Hafizah Indriany; Apriani Putri Fajtriansyah; Herlini Puspika Sari (4, 2026)
Gender issues in Islamic education have become an important topic in contemporary educational discourse, especially in efforts to achieve equitable access to learning for men and women. Normatively, Islamic teachings emphasize the principles of justice and equality in obtaining education. However, in practice, there are still various challenges that affect the implementation of gender equality in Islamic education environments, such as social stereotypes, the influence of patriarchal culture, and limited understanding of gender-responsive education. This article aims to analyze gender issues in Islamic education and identify various challenges and strategies in realizing equitable access to learning. This study uses a qualitative approach with library research. Data were collected through documentary studies of various scientific literature sources in the form of books, journal articles, and relevant research results published in recent years. Data analysis was conducted using content analysis techniques to critically examine various concepts, ideas, and research findings related to gender equality in Islamic education. The results of the study indicate that gender inequality in Islamic education is more influenced by social and cultural constructs than by Islamic teachings themselves. Therefore, it is necessary to strengthen gender-responsive curricula, improve educator competencies, and support inclusive education policies. These findings contribute conceptually to the development of a more equitable and inclusive Islamic education, and emphasize the importance of integrating a gender perspective into the education system to achieve equitable access to learning. Abstrak Isu gender dalam pendidikan Islam menjadi salah satu topik penting dalam diskursus pendidikan kontemporer, terutama dalam upaya mewujudkan keadilan akses belajar bagi laki-laki dan perempuan. Secara normatif, ajaran Islam menegaskan prinsip keadilan dan kesetaraan dalam memperoleh pendidikan. Namun, dalam praktiknya masih terdapat berbagai tantangan yang memengaruhi implementasi kesetaraan gender di lingkungan pendidikan Islam, seperti stereotip sosial, pengaruh budaya patriarki, serta terbatasnya pemahaman tentang pendidikan yang responsif gender. Artikel ini bertujuan untuk menganalisis isu gender dalam pendidikan Islam serta mengidentifikasi berbagai tantangan dan strategi dalam mewujudkan keadilan akses belajar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data dikumpulkan melalui studi dokumentasi terhadap berbagai sumber literatur ilmiah berupa buku, artikel jurnal, dan hasil penelitian relevan yang diterbitkan dalam beberapa tahun terakhir. Analisis data dilakukan dengan teknik analisis isi untuk menelaah secara kritis berbagai konsep, gagasan, dan temuan penelitian yang berkaitan dengan kesetaraan gender dalam pendidikan Islam. Hasil penelitian menunjukkan bahwa ketimpangan gender dalam pendidikan Islam lebih banyak dipengaruhi oleh konstruksi sosial dan budaya daripada ajaran Islam itu sendiri. Oleh karena itu, diperlukan penguatan kurikulum responsif gender, peningkatan kompetensi pendidik, serta dukungan kebijakan pendidikan yang inklusif. Temuan ini memberikan kontribusi konseptual bagi pengembangan pendidikan Islam yang lebih adil dan inklusif, serta menegaskan pentingnya integrasi perspektif gender dalam sistem pendidikan untuk mewujudkan keadilan akses belajar.